SAT0350 Content and face validity and feasibility of five candidate instruments for psoriatic arthritis randomised controlled trials: results from the psa omeract core set workshop at the grappa 2017 annual meeting. (12th June 2018) - Holland, R.; Tillett, W.; Ogdie, A.; Leung, Y.Y.; Gladman, D.D.; Callis Duffin, K.; Coates, L.C.; Mease, P.; Eder, L.; Strand, V.; Elmamoun, M.; Højgaard, P.; et al.
Abstract : Background: The Group for Research and Assessment of Psoriasis and Psoriatic Arthritis (GRAPPA) – Outcome Measures in Rheumatology (OMERACT) Psoriatic Arthritis (PsA) Core Set working group is developing a core instrument set to guide selection of outcome measures (instruments) for PsA randomised controlled trials (RCTs) and longitudinal observational studies (LOS). Candidate instrument measurement properties are being appraised in systematic literature reviews by working group members. Objectives: Appraise the content and face validity (domain match) and feasibility of PsA instruments with GRAPPA stakeholders using the OMERACT Filter 2.1 instrument selection process 1 . Methods: The PsA Core set workshop held at the GRAPPA 2017 annual meeting comprised an introductory plenary session and breakout group discussions. Working group members facilitated six breakout groups, with two patient research partners (PRPs) per group, discussing pre-selected domain-instrument pairs. Participants individually reviewed the instrument(s). After group discussion, they completed anonymised paper-based OMERACT questionnaires examining domain match and feasibility, with votes for each aspect of domain match and feasibility centralised by instrument. A final vote (show of hands) on whether the assigned instrument met the requirements for domain match and feasibility using the OMERACT traffic-light scoring system was taken. Consensus was defined as more than 70% agreement, and majority as more than 50% agreement within a group. Consensus represents stronger evidence than majority agreement. Results: There were 145 participants across all breakout groups and 116 returned completed questionnaires. Anonymized votes are summarised across groups and instruments in figure 1. More than 70% in the respective breakout groups endorsed the PsA instrument 66 swollen and 68 tender joint count (66/68 SJC/TJC) as a good match with the target domain of arthritis, a subset of MSK disease activity, FACIT-Fatigue as a good match with fatigue, and PsAID12 as a good match with HRQoL. There was consensus or majority agreement for all feasibility questions for the 66/68 SJC/TJC, HAQ-DI and PsAID9 and PsAID12. For the SPARCC enthesitis index only one item in both domain match and feasibility did not reach majority agreement. Conclusions: The first two steps of the OMERACT Filter 2.1 instrument selection process for five candidate instruments have been completed. The first set of candidate instruments selected to undergo the next phase of the OMERACT Filter 2.1, construct validity and discrimination appraisal are 66/68 SJC/TJC, SPARCC enthesitis index, PsAID9, PsAID12, HAQ-DI and FACIT-Fatigue. Additional PsA instruments will undergo the OMERACT selection process. Reference: [1] Boers M, Kirwan JR, Tugwell P, et al. The OMERACT Handbook. Accessed 8 January 2018. https://www.omeract.org/resources. Disclosure of Interest: None declared